Occupational therapy in cerebellar ataxia and the resource to assistive technology: a case study - Cabrera Corvelo Delboni, Miriam; da Conceição dos Santos, Maria; Asola, Giovana (O Mundo da Saúde, 2006)
Ataxia Cerebellar is a consequence of injuries in the region of the cerebellum that compromise the functions of balance and dexterity, causing a continuous tremor in all the muscular groups. This case study relates to a patient with exogenous after-poisoning encephalopatia that caused a cerebellar ataxia condition that was treated in the School Clinics São Camilo. An evaluation in Occupational Therapy in September 2005 by the instrument Functional Independence Measure (FIM) detected a condition of total dependence as regards feeding (level 1). Resources of assistive technology were projected aiming to reduce tremors, including trunk stabilizer, adaptations of table height, plate with taller edges and cutlery thickening aiming at the improvement of feeding independence. The evaluation of feeding by FIM, before and after daily e use of the adaptations developed by Occupational Therapy proved the effectiveness of the resources of assistive technology as a factor favoring functional independence and presenting the secondary benefit of improving the quality of leisure activities.